Applications of regenerative techniques in adult orthodontics - Liu, Catherine; Sharpe, Paul; Volponi, Ana Angelova (Frontiers in Dental Medicine, 2023)
Management of the growing adult orthodontic patient population must contend with challenges particular to orthodontic treatment in adults. These include a limited rate of tooth movement, increased incidence of periodontal complications, higher risk of iatrogenic root resorption and pulp devitalisation, resorbed edentulous ridges, and lack of growth potential. The field of regenerative dentistry has evolved numerous methods of manipulating cellular and molecular processes to rebuild functional oral and dental tissues, and research continues to advance our understanding of stem cells, signalling factors that stimulate repair and extracellular scaffold interactions for the purposes of tissue engineering. We discuss recent findings in the literature to synthesise our understanding of current and prospective approaches based on biological repair that has the potential to improve orthodontic treatment outcomes in adult patients. Methods such as mesenchymal stem cell transplantation, biomimetic scaffold manipulation, and growth factor control may be employed to overcome the challenges described above, thereby reducing adverse sequelae and improving orthodontic treatment outcomes in adult patients. The overarching goal of such research is to eventually translate these regenerative techniques into clinical practice, and establish a new gold standard of safe, effective, autologous therapies.